Corporate Culture Through the Prism of Behavioral Economics - Milanova, Adelina (Research Papers, 2020)
The influence of corporate culture in the context of corporate governance is determined not only by the observance of certain social and organizational rules and norms, but also by the irrational) effects such as sympathy, antipathy, ambition, sense of superiority, sense of vengeance, , which in many cases hinder or even block the rational management decisions and processes. Relying on the behavioral paradigm implies a new vision of the manifestation of corporate human capital and mechanisms for effective corporate governance.